Impacts of socio-technical innovation bundling on empowerment, resilience and food and nutrition security in Kenya - Ouya, Fredrick; Lutomia, Cosmas; Nchanji, Eileen; Waswa, Boaz; Ooro, Patrick; Muriithi, Catherine; Njiru, Emerita; Ingasia, Oscar; Otieno, Arnold; Okutoyi, Getrude (2024)
Adoption of Socio-Technical Innovation Bundles Socio-technical innovation bundles are context specific combination or combinations of technological (e.g., seed and fertilizer), technical (e.g., training and capacity building and development), and social (e.g., institutions, policy, social organizations, financial mechanisms, etc.) innovations. • There was a high adoption of technological innovations (99%) compared to social innovations (89%) and technical innovations (72%) • 63% of surveyed farmers adopted STIBs. • STIBs adoption was higher among UU farmers (98%) compared to non-UU farmers (33%) this could be attributed to their participation in the UU initiative. • STIBs adoption rate among women in Embu and Makueni was slightly lower than the rate of STIBs among men.